Subaltern Consciousness and Global Solidarity in Aahuti’s "Gahungoro Africa” - Sunar, Krishna Bahadur (Kaumodaki: Journal of Multidisciplinary Studies, 2026)
This paper examines Aahuti’s “Gahungoro Africa” through the lens of subaltern theory, analyzing its role in articulating Dalit resistance against caste-based discrimination. The poem not only foregrounds the experiences of Dalits but also situates their struggle within a broader global context of systemic subjugation. By drawing parallels between Dalit marginalization and historical forms of racial and colonial oppression in Africa, Aahuti challenges hegemonic structures that perpetuate inequality. The poem transforms the historically silenced Dalit subject into an active agent demanding dignity, justice, and liberation. Employing the theoretical frameworks of Antonio Gramsci, Ranajit Guha, and Gayatri Spivak, this study investigates how “Gahungoro Africa” disrupts dominant narratives that erase Dalit voices. It explores how the poem critiques religious and social institutions that uphold caste hierarchy, positioning subaltern resistance as central to socio- political transformation. By connecting the Dalit struggle to the global histories of oppression, “Gahungoro Africa” asserts the universality of marginalized voices and their right to justice. This paper argues that Aahuti’s poem is not merely a lamentation but a radical assertion of identity, a call for socio-political change, and aims to dismantle the ‘Caste- System’ to form an inclusive society that acknowledges the voices of the oppressed.